2020
DOI: 10.1016/j.celrep.2020.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal BIN1 Regulates Presynaptic Neurotransmitter Release and Memory Consolidation

Abstract: Highlights d The loss of BIN1 in neurons leads to impaired spatial memory consolidation d Neuronal Bin1 cKO mice have deficits in excitatory synaptic transmission d BIN1 regulates presynaptic vesicular release in hippocampal excitatory synapses d The results highlight a non-redundant role for BIN1 in presynaptic regulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 73 publications
3
66
0
Order By: Relevance
“…In addition, acute knockdown of Bin1 in primary cortical neurons reduced calcium spikes in response to NMDA (McAvoy et al, 2019). Similarly, a chronic genetic deletion of Bin1 in mice decreased mEPSCs frequency, suggesting a an effect of Bin1 on synaptic transmission (De Rossi et al, 2020). Complementary to these studies on effects of decreased Bin1 expression in mice, we found that increased human BIN1 expression increases synaptic transmission, neuronal activity, and calcium transients, and that BIN1 interacts with LVGCCs in neurons.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, acute knockdown of Bin1 in primary cortical neurons reduced calcium spikes in response to NMDA (McAvoy et al, 2019). Similarly, a chronic genetic deletion of Bin1 in mice decreased mEPSCs frequency, suggesting a an effect of Bin1 on synaptic transmission (De Rossi et al, 2020). Complementary to these studies on effects of decreased Bin1 expression in mice, we found that increased human BIN1 expression increases synaptic transmission, neuronal activity, and calcium transients, and that BIN1 interacts with LVGCCs in neurons.…”
Section: Discussionsupporting
confidence: 63%
“…BIN1 is present at pre‐ and post‐synaptic sites and in axons, as shown by super‐resolution microscopy and immuno‐electron microscopy in primary hippocampal neurons and CA3‐CA1 synapses (De Rossi et al., 2020; Schürmann et al., 2019). Post‐synaptically, BIN1 is enriched at extra‐synaptic sites within the mouse cortex (Schürmann et al., 2019); given that CME largely occurs at sites adjacent to the post‐synaptic density (PSD) (Triller & Choquet, 2005), the localisation of BIN1 supports its involvement in the CME of tau at post‐synaptic sites and suggests a role for BIN1 in its trans‐synaptic spread.…”
Section: Mechanisms For Neuronal Entry Of Taumentioning
confidence: 98%
“…BIN1 , another AD modifier identified by GWAS in humans ( 59 ), also plays a role in endocytosis ( 60 ) and has recently been shown to regulate neurotransmitter release in mouse glutamatergic neurons ( 22 ). The overexpression of Amph, the fly homologue of BIN1, led to a slight rescue in lifespan ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether BIN1 plays a role in Aβ toxicity has also not been investigated. Recently, BIN1 was shown to be involved in neurotransmitter release in mouse hippocampal neurons ( 22 ).…”
Section: Introductionmentioning
confidence: 99%